Thought Seeds in Anthrogogic Learning Contexts - Deepa, Shree (JOURNAL OF INDIAN EDUCATION, 2022)
This paper reopens and re-examines the argument that there are clear differences between pedagogy and adult learning, against the backdrop of NEP 2020. It introduces two new paradigms: ‘anthrogogy’ and ‘thought seeds’ by tracing the former to andragogy and developing the latter from tasks. The paper defines a thought seed, outlines its characteristics, and then goes on to examine the differences between tasks and thought seeds. Moving from a theoretical argument to practice, the paper further briefly scrutinises these contrasts through some critiques of tasks meant for higher education learners and demonstrates how they can mature into thought seeds.